Associative electrolyte solution near the charge hard wall. Density, charge, polarization and potential profiles - Kapko, V.I.; Holovko, M.F. (Condensed Matter Physics, 2001)
The density, charge, polarization and potential profiles of a simple model of an associative electrolyte are studied in an associative mean spherical approximation (AMSA). The limits of the full association and complete disassociation are considered.